FORMATION AND DEVELOPMENT OF CREATIVE THINKING THROUGH CHESS GAMES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the process of forming and developing creative thinking in primary school students through chess games. Chess is not only a game that develops logical thinking, but also plays an important role in the formation of students' independent, analytical and innovative thinking skills. The article discusses the impact of chess on creative thinking, its contribution to the intellectual development of students, and methods for effectively using chess in the modern education system. During the study, the impact of chess classes on creative thinking was studied on an experimental basis, and its positive results are presented.